The effects of long-term application of fomesafen on weed seedbank and resistance levels of Amaranthus retroflexus L. - Guo, Xiaotong; Guo, Yulian; Wang, Yu; Luo, Chan; Cong, Keqiang (Frontiers in Plant Science, 2024)
Amaranthus retroflexus L. is one of the invasive malignant weeds in soybean fields. The diphenyl ether herbicides are commonly used to control weeds in soybean fields currently, among which fomesafen is the most widely used. With the long-term use of fomesafen, the weed species in soybean fields in multiple areas was declined, and the control effect of fomesafen against Amaranthus retroflexus was decreased significantly. The study aims to confirm the effects of long-term use of fomesafen on weed community richness and the current resistance level of Amaranthus retroflexus. In this paper, the result of seed germination indicated that the weed community richness was decreased significantly due to the long-term application of fomesafen, and the primary dominant weed was Amaranthus retroflexus. The result of the whole-plant bioassay denoted that Amaranthus retroflexus has developed the resistance to fomesafen, and resistance index was 50~59 g a.i. ha-1. The resistance level and mechanism of Amaranthus retroflexus were clarified by target gene detection, enzyme activity determination and gene expression analysis. The results performed that there were both target resistance with Arg128Gly mutation in PPX2 gene and non-target resistance (NTSR) with increased activity of metabolic enzyme (cytochromes P450 (P450s) and glutathione S-transferase (GSTs)) and protective enzyme (peroxidase (POD) and catalase (CAT)) in Amaranthus retroflexus.